Pengaruh Daya Tarik Wisata Terhadap Minat Berkunjung Kembali Ke Wisata Sajuta Janjang Kabupaten Agam - Firda Aulia Rahmi; Feri Ferdian (Lembaga Pengembangan Kinerja Dosen, 2023)
This research discusses the impact of tourist attractions on interest in returning to the Sajuta Janjang in Agam Regency, which is motivated by a significant decrease in the visits every year number, pre-research which states that as many as 72% of visitors are not interested in visiting again and there are still negative comments on Google review about Sajuta Janjang. The method for research used is a technique of quantitative method with a approach in causal associative and the technique for sampling uses a purposive sampling which is determined at 220 samples. The technique for data collection uses a questionnaire prepared on a Likert scale which has been tested for validity and reliability. The technique for data analysis uses PLS-SEM software. The R square results show that tourist attraction has a big influence on interest in returning to visit with a percentage value of 70.5% while the remaining percentage of 29.5% is influenced by other factors. The test of hypothesis results obtained a t-statistic of 48.1 > 1.96 and a p value of 0.00 < 0.05, so the research results indicate that the tourist attraction variable has a significant effect on interest in returning to visit. In this research, the conclusion that Ha was accepted and Ho was rejected.